Ang Imahe ng mga Macabebe sa mga Litrato ng American Mass Media (1899-1901) - Iniego, Florentino A. (Philippine Social Sciences Review; Recent Studies in Philippine History, Eds., Laura Samson and Ricardo Jose, 2010)
This paper analyzes the image of the Macabebes in the photos published in American mass media during the early years of the Filipino-American War. The town of Macabebe (“bordering riverbanks”) in Pampanga is one of the oldest pre-colonial towns in Central Luzon. The Macabebes heroically resisted initial attempts of colonization by the forces of Miguel Lopez de Legazpi in 1571. But later on they faithfully served the Spanish colonizers for more than three centuries. When the Spanish forces fell in Pampanga, they switched loyalties to the American imperialists in 1899. Called “Little Macs,” they were mobilized by General Frederick Funston in a covert mission that resulted in the arrest of General Emilio Aguinaldo in Palanan, Isabela on 23 March 1901. The American imperialists have succeeded in legitimizing their control of the Philippines through the visual and textual messages conveyed by photographs, captions and narratives about the Macabebes. They created distorted notions and negative stereotyping of the Macabebes as “traitors,” “mercenaries,” and “dog-blooded,” which settled in the historical consciousness of Kapampangans and Filipinos. This “fakelore,” that was inscribed in the oral and written literature down to the folk consciousness of the Filipinos should be countered and clarified toward a just reading, writing and teaching of history.